PEMANFAATAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KEAKTIFAN ANAK USIA DINI DI TK KOBER-DAYCARE LAB UPI BUMI SILIWANGI - Wahyuni Rahayu Ningsih; Salwa Oktavia; Divani Vesaviana; Ulwiyatus Saadah; Naely Alfibhusniatin; Irfan Haris (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning media play an important role in creating active and meaningful learning experiences in early childhood education. This study aimed to describe the utilization of learning media to improve children's activeness at TK Kober-Daycare Lab UPI Bumi Siliwangi. A qualitative approach with a descriptive design was employed. Data were collected through observations, semi-structured interviews with the principal and a teacher, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that teachers utilized various learning media, including concrete media, educational play tools, visual media, natural materials, and play-based media implemented in the Art and Craft, Letters and willingness to ask and answer questions, express ideas, collaborate with peers, and actively participate in learning activities. The appropriate use of learning media based on children's developmental characteristics supports active, enjoyable, and child-centered learning.